'Don't look down!': A short history of rooftopping photography. Issue 7 (2nd October 2016) - Deriu, Davide
Abstract : The article examines the practice known as 'rooftopping photography' and its significance for the representation of vertical cities. It begins by charting the historical development of architecture as a viewing platform in the age of the camera, and dwells on the imagery of cityscapes from above that emerged in the inter-war period. Against this background, the essay investigates how rooftopping arose out of the urban exploration movement and became a global trend in the early 2010s. This phenomenon is situated within its wider social and cultural context, and is discussed with reference to the online media discourse that contributed to its public visibility. A set of ideas from the philosophy of photography and visual culture inform the critical analysis of rooftopping photographs: this broad and diverse body of images is examined with a focus on two predominant modes of representation—panoramic and plunging views. The affective responses elicited by so-called 'vertigo-inducing' images are discussed through the concept of vicarious kinaesthesia, which offers insights into the nexus between visceral experience and visual representation that lies at the core of rooftopping. By unpacking this interplay, the essay explores a phenomenon that has hitherto been given little scholarly attention and reflects on its broader implications for the relationship between photography and architecture today.